Learning Motivation of High-Achieving Students in Second Grade of Integrated Islamic Junior High School LHI Bantul Yogyakarta - Eko Prasetyo; Krisma Dewi (Edumaspul: Jurnal Pendidikan, 2024)
Learning motivation is an important element in achieving maximum learning results. Different learning motivations between students can result in different outcomes. This research aims to describe the learning motivation of high-achieving students in the second grade of the Integrated Islamic Junior High School LHI Bantul Yogyakarta. The research subjects were 12 high-achieving students taken from 4 parallel classes, 3 students from each class. The research method used is qualitative. Data collection techniques were carried out using documentation, observation, and interviews. The results of the research show that there are two types of learning motivation for high-achieving students in the second grade of the Integrated Islamic Junior High School LHI Bantul Yogyakarta, namely intrinsic motivation that comes from within the students themselves and extrinsic motivation that comes from external factors. Several influencing factors include motivation from within oneself, motivation from outside, involvement in choosing a school, stimulation from teachers, stimulation from parents, and stimulation from the surrounding environment. Therefore, factors that support the learning motivation of high-achieving students need to be strengthened and implemented with other students so that all students can improve their learning achievement.